Approximate Calculation of the Thermal Regime of Reservoirs Formed by a Frozen Dam (Priblizhennyi Raschet Teplovogo Rezhima Vodokhranilishch Obrazovannykh Pomorozhennoi Plotinoi) - Pekhovich,A I; Kudoyarov,L I; Zhidkikh,V M (1977)
The goal of this paper is to provide a general scheme and practical method for calculating the thermal regime of a reservoir, taking into consideration interaction with the dam and the foundation. It also examines the possibility of regulating the thermal regime of the structure. (Author) Trans. of Vsesoiuznyi mauchno-issledovatelskii institut gidrotekhniki. Izvestiia, Leningrad (USSR) v100 p146-153 1972.